Highly Potent and Vastly Conditional Instructional Practices: Variations in Use and Utility of Language Interactions for Kindergarten. Issue 4 (18th May 2020) - Neugebauer, Sabina; Sandilos, Lia; Coyne, Michael; McCoach, D. Betsy; Ware, Sharon
ABSTRACT: Research Findings: This study of kindergarten monolingual and Dual Language Learners (DLLs) (N=263; mean age = 63.40 months) and their teachers (N=27) found significant mean differences in the observed quality of language interactions in classrooms with differing proportions of DLLs. Teachers instructing in classrooms with higher numbers of DLLs had lower levels of concept development and quality of feedback. Moderation findings revealed that interactions supporting concept development were particularly beneficial for DLLs' vocabulary growth. Practice and Policy: Study results underscore the importance of using language interaction practices that cultivate higher-order thinking with DLLs.